2000
DOI: 10.1007/s004110000059
|View full text |Cite
|
Sign up to set email alerts
|

Strontium metabolism in teeth and enamel dose assessment: analysis of the Techa river data

Abstract: People living on the banks of the Techa river were exposed to 90Sr in the early 1950s. Data obtained by radiochemical measurements of extracted permanent teeth, 90Sr autopsy measurements in bone and tooth samples, in vivo measurements of surface beta activity of the anterior teeth and whole-body counter (WBC) measurements of 90Sr in the skeleton have been analyzed. Surface beta activity measurements indicate a biological half-life of 90Sr of about 35 years in enamel. The WBC measurements have been performed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Gy in the teeth that had already been completed at that time (Tolstykh et al, 2000;Romanyukha et al, 2001). Because of the differences in the development processes of teeth in different buccal positions, incorporation of radioisotopes into teeth of different types occurs at different ages.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
See 4 more Smart Citations
“…Gy in the teeth that had already been completed at that time (Tolstykh et al, 2000;Romanyukha et al, 2001). Because of the differences in the development processes of teeth in different buccal positions, incorporation of radioisotopes into teeth of different types occurs at different ages.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
“…These factors make the volume-averaged dose provided by EPR measurements of little significance for short-range particles. Tolstykh et al (2000Tolstykh et al ( , 2003 argued against the suitability of EPR dosimetry with 90 Sr contaminated teeth, in particular because the estimate of the tooth enamel dose should account for the time dependence of the 90 Sr content and distribution not only in enamel, but also, and especially, in dentine. They concluded that EPR tooth enamel dosimetry should be limited to the assessment of the external dose component.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
See 3 more Smart Citations